Alfvénic Dynamics and Fine Structuring of Discrete Auroral Arcs: Swarm and e‐POP Observations. Issue 2 (24th January 2018) - Miles, D. M.; Mann, I. R.; Pakhotin, I. P.; Burchill, J. K.; Howarth, A. D.; Knudsen, D. J.; Lysak, R. L.; Wallis, D. D.; Cogger, L. L.; Yau, A. W.
Abstract: The electrodynamics associated with dual discrete arc aurora with antiparallel flow along the arcs were observed nearly simultaneously by the enhanced Polar Outflow Probe (e‐POP) and the Swarm A and C spacecraft. Auroral imaging from e‐POP reveals 1–10 km structuring of the arcs, which move and evolve on second timescales and confound the traditional single‐spacecraft field‐aligned current algorithms. High‐cadence magnetic data from e‐POP show 1–10 Hz, inferred Alfvénic, perturbations coincident with and at the same scale size as the observed dynamic auroral fine structures. High‐cadence electric and magnetic field data from Swarm A reveal nonstationary electrodynamics involving reflected and interfering Alfvén waves and modulation consistent with trapping in the ionospheric Alfvén resonator (IAR). These observations suggest a role for Alfvén waves, perhaps also the IAR, in discrete arc dynamics on 0.2–10 s timescales and 1–10 km spatial scales and reinforce the importance of considering Alfvén waves in magnetosphere‐ionosphere coupling. Plain Language Summary: An ongoing question in space physics is whether the energy that powers the vibrant and dynamic aurora is the result of static electric fields or magnetic waves. We address this question using data from three observational satellites, e‐POP, Swarm A, and Swarm C. We compare electric and magnetic field measurements at the locations of the spacecraft to high‐speed images of the aurora below as the satellites traveled over northern Canada. We show that as the satellites traveled over the aurora they detected magnetic waves known as Alfvén waves. We argue that these waves play an important and underappreciated role in transporting energy from near‐Earth space to the atmosphere in order to power the aurora. Key Points: High‐resolution e‐POP magnetic and auroral data reveal coherent, inferred Alfvénic, dynamics and structuring of discrete auroral arcs Multipoint high‐cadence Swarm E ‐ and B ‐ field data reveal nonstationary electrodynamics involving reflected and interfering Alfvén waves Suggests a role for Alfvén waves and possibly ionospheric Alfvén resonator (IAR) in discrete arc dynamics on 0.2–10 s and 1–10 km scales